2002
DOI: 10.1034/j.1600-0536.2002.460302.x
|View full text |Cite
|
Sign up to set email alerts
|

Fragrance contact dermatitis – a worldwide multicenter investigation (Part III)

Abstract: The purpose of this study was to determine the frequency of responses to selected fragrance materials in patients who were fragrance sensitive. 218 fragrance sensitive subjects were evaluated in eight centres worldwide with a fragrance mixture (FM) and 17 less well-studied fragrance materials. Reaction to the fragrance mixture (FM) occurred in 76% of the subjects. The (FM) detected all reactions to nerol and hydroxycitronellol and 93% of the reactions to clove bud oil. Ten fragrance materials were not detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 19 publications
1
24
0
4
Order By: Relevance
“…Previous studies have implied that it may be an important allergen and the most recent study from Germany (1) found a prevalence of contact allergy of 0.5% among 6573 consecutively patch tested eczema patients. Two other studies conducted in fragrance allergic subjects showed prevalence of contact allergy of 3.2% (2) among 217 subjects and 5.4% among 167 subjects (3).…”
mentioning
confidence: 83%
“…Previous studies have implied that it may be an important allergen and the most recent study from Germany (1) found a prevalence of contact allergy of 0.5% among 6573 consecutively patch tested eczema patients. Two other studies conducted in fragrance allergic subjects showed prevalence of contact allergy of 3.2% (2) among 217 subjects and 5.4% among 167 subjects (3).…”
mentioning
confidence: 83%
“…101 In answer to this, an additional mixture called fragrance mix II has been added to many screening series. Fragrance mix II (14% in petrolatum) is a mixture of 6 fragrance allergens (citronellol 0.5%, Lyral (hydroxyisohexyl 3-cyclohexene carboxaldehyde) 2.5%, hexyl cinnamal 5.0%, citral 1.0%, coumarin 2.5%, and farnesol 2.5%).…”
Section: Thimerosalmentioning
confidence: 99%
“…Naquele estudo a alergia por perfumes acometeu preferencialmente mulheres, em face e mãos, sendo que muitos pacientes relataram história pessoal pregressa de rinite, asma ou dermatite atópica [36].…”
Section: /8unclassified